Association of Latitude and Exposure to Ultraviolet B Radiation With Severity of Multiple Sclerosis: An International Registry Study. (14th June 2022) - Vitkova, Marianna; Diouf, Ibrahima; Malpas, Charles; Horakova, Dana; Kubala Havrdova, Eva; Patti, Francesco; Ozakbas, Serkan; Izquierdo, Guillermo; Eichau, Sara; Shaygannejad, Vahid; Onofrj, Marco; Lugaresi, Alessandra; et al.
Abstract : Background and Objectives: The severity of multiple sclerosis (MS) varies widely among individuals. Understanding the determinants of this heterogeneity will help clinicians optimize the management of MS. The aim of this study was to investigate the association between latitude of residence, UV B radiation (UVB) exposure, and the severity of MS. Methods: This observational study used the MSBase registry data. The included patients met the 2005 or 2010 McDonald diagnostic criteria for MS and had a minimum dataset recorded in the registry (date of birth, sex, clinic location, date of MS symptom onset, disease phenotype at baseline and censoring, and ≥1 Expanded Disability Status Scale score recorded). The latitude of each study center and cumulative annualized UVB dose at study center (calculated from National Aeronautics and Space Administration's Total Ozone Mapping Spectrometer) at ages 6 and 18 years and the year of disability assessment were calculated. Disease severity was quantified with Multiple Sclerosis Severity Score (MSSS). Quadratic regression was used to model the associations between latitude, UVB, and MSSS. Results: The 46, 128 patients who contributed 453, 208 visits and a cumulative follow-up of 351, 196 patient-years (70% women, mean age 39.2 ± 12 years, resident between latitudes 19°35′ and 56°16′) were included in this study. Latitude showed a nonlinear association with MS severity. In latitudes <40°, more severe disease was associated with higher latitudes (β = 0.08, 95% CI 0.04–0.12). For example, this translates into a mean difference of 1.3 points of MSSS between patients living in Madrid and Copenhagen. No such association was observed in latitudes <40° (β = −0.02, 95% CI −0.06 to 0.03). The overall disability accrual was faster in those with a lower level of estimated UVB exposure before the age of 6 years (β = − 0.5, 95% CI −0.6 to 0.4) and 18 years (β = − 0.6, 95% CI −0.7 to 0.4), as well as with lower lifetime UVB exposure at the time of disability assessment (β = −1.0, 95% CI −1.1 to 0.9). Discussion: In temperate zones, MS severity is associated with latitude. This association is mainly, but not exclusively, driven by UVB exposure contributing to both MS susceptibility and severity.